2010
DOI: 10.1007/s10900-010-9242-9
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Training and Smoking Cessation Services Provided in Community Pharmacies in Thailand

Abstract: Over the past few years, several training programs have been run in support of smoking cessation services within community pharmacy circles in Thailand. These have included a comprehensive training program offered by the Thai Pharmacy Network for Tobacco Control (TPNTC) and brief training programs run by other agencies. This study provides an estimate of the scale of smoking cessation activities among Thai pharmacies, and examines the impact of both the brief and comprehensive training programs on the provisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 27 publications
2
28
1
Order By: Relevance
“…In the present survey, lack of knowledge or clinical skills was the most commonly reported barrier to the provision of public health service in community pharmacy followed by lack of access to additional training programs and lack of personnel or resources. Similar barriers have also been documented in different parts of the globe including lack of time and personnel, lack of clinical skills and tools [7][8][9][10]. Public's lack of awareness of community pharmacy professional's role in public health and uncooperative patients were other important barriers identified in the literature but had not been prominent in our study [26,27].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the present survey, lack of knowledge or clinical skills was the most commonly reported barrier to the provision of public health service in community pharmacy followed by lack of access to additional training programs and lack of personnel or resources. Similar barriers have also been documented in different parts of the globe including lack of time and personnel, lack of clinical skills and tools [7][8][9][10]. Public's lack of awareness of community pharmacy professional's role in public health and uncooperative patients were other important barriers identified in the literature but had not been prominent in our study [26,27].…”
Section: Discussionsupporting
confidence: 77%
“…Lack of knowledge and skills, lack of confidence and adequate training, lack of policies, poor recognition within the healthcare system, patients' reluctance to use pharmacy services and presence of inadequate number of pharmacy staff are some of the factors which can contribute to the low level of pharmacy services uptake and public health initiatives [7][8][9][10][11]. In developed countries, such as the United Kingdom, pharmacists are well integrated into public-health programs [12].…”
Section: Introductionmentioning
confidence: 99%
“…When assessing the quality of the evidence by peer‐review following the criteria in Table , 18 studies were acceptable and eligible for analysis (Figure ). Of the 18 articles, one article provided more than one outcome; thus, the total number of papers when grouping by outcomes was 20 . Ten studies were excluded due to a high dropout rate and/or small sample size, as shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 18 included studies, there were 10 clinical outcome studies, two qualitative studies, three survey studies, and three economic studies that met all of the quality assessment criteria. Three studies were randomized controlled trials, three studies were clinical trials with a control group, and four were clinical trials without a control group .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation